Pengaruh Disiplin Dan Lingkungan Kerja Fisik Terhadap Produktivitas Pegawai Pada Dinas Koperasi, Perindustrian Dan Perdagangan Kota Bima - Ali Khasbi Akbar; Jaenab Jaenab (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This type of research is associative research which aims to determine the effect of discipline and the physical work environment on the work productivity of employees at the Office of Cooperatives, Industry and Trade in Bima City. The population in this study were all employees at the Office of Cooperatives, Industry and Trade in the City of Bima, consisting of 60 employees. The sample was determined by purposive sampling technique with 40 ASN respondents. Data collection methods used are observation, questionnaires (questionnaire), library research, and documentation. Data analysis techniques used in this study were instrument tests (validity and reliability tests), multiple linear regression analysis, correlation coefficients, coefficients of determination, T tests, and f tests, using the SPSS v26 program. This analysis includes: validity test, reliability test, classic assumption test, multiple regression analysis, analysis of the coefficient of determination (R2), analysis of the correlation coefficient (R), and hypothesis testing through t test and f test. The results of the analysis using the t test can be seen that one independent variable, namely work discipline (X1) and physical work environment (X2) has a positive and partially significant effect on the dependent variable, namely employee work productivity (Y). Then the results of the analysis using the F test can be seen that the three independent variables, namely work discipline (X1), and the physical work environment (X2) together have a positive and significant effect on the dependent variable, namely employee productivity (Y).